2007
DOI: 10.1111/j.1875-595x.2007.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental erosion amongst 13- and 14-year-old Brazilian schoolchildren

Abstract: These data are the first to show that in a cohort of 13-14-year old Brazilian schoolchildren, approximately one third of those examined showed mild erosion, requiring clinical preventive counselling. No statistically significant association was observed between erosion, gender and socioeconomic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
64
10
36

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(135 citation statements)
references
References 19 publications
25
64
10
36
Order By: Relevance
“…Relative to erosive lesions, 18.4% of the sample presented lesion in at least one tooth, similar to the findings of Gurgel et al 8 and Mangueira et al 10 . Over the course of the last decade there has been a significant increase in the prevalence and severity of erosive dental wear, particularly in children and adolescents 9,14,27 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Relative to erosive lesions, 18.4% of the sample presented lesion in at least one tooth, similar to the findings of Gurgel et al 8 and Mangueira et al 10 . Over the course of the last decade there has been a significant increase in the prevalence and severity of erosive dental wear, particularly in children and adolescents 9,14,27 .…”
Section: Discussionsupporting
confidence: 80%
“…Twenty individuals were examined, and exams were repeated until the examiners knew the criteria well. However, it was not possible to perform clinical observation of all the grades suggested by the O´Sullivan 6 index, which involved the use of intra-oral color photographic images [8][9][10] for discussing the clinical aspects of each grade and mounting matrices for comparison of the diagnoses and performing the Cohen kappa test 13 . The Kappa inter and intra-examiner values obtained were 0.74 and 0.82, respectively.…”
Section: Training and Calibration Processmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that the prevalence of dental erosion is gradually increasing (Auad et al 2007). Turkey has a young population of 20 million children aged 0 to 16 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The results of other surveys varied. For example, Auad et al (2007) and Mangueira et al (2009) reported that the palatal surfaces were the most affected. The consumption of erosive drinks and food was also shown to be strongly associated with erosion on the facial and occlusal surfaces, while severe palatal erosion occurred infrequently and were highly associated with chronic vomiting (Lussi et al 1991).…”
mentioning
confidence: 99%